Protein Inhibitor of Activated STAT (PIAS) Negatively Regulates the JAK/STAT Pathway by Inhibiting STAT Phosphorylation and Translocation - Niu, Guo-Juan; Xu, Ji-Dong; Yuan, Wen-Jie; Sun, Jie-Jie; Yang, Ming-Chong; He, Zhong-Hua; Zhao, Xiao-Fan; Wang, Jin-Xing (Frontiers in Immunology, 2018)
Protein inhibitor of activated STAT (PIAS) proteins are activation-suppressing proteins for signal transducer and activator of transcription (STAT), which involves gene transcriptional regulation. The inhibitory mechanism of PIAS proteins in the Janus kinase (JAK)/STAT signaling pathway has been well studied in mammals and Drosophila. However, the roles of PIAS in crustaceans are unclear. In the present study, we identified PIAS in kuruma shrimp Marsupenaeus japonicus and found that its relative expression could be induced by Vibrio anguillarum stimulation. To explore the function of PIAS in shrimp infected with V. anguillarum, we performed an RNA interference assay. After knockdown of PIAS expression in shrimp subjected to V. anguillarum infection, bacterial clearance was enhanced and the survival rate increased compared with those in the control shrimp (dsGFP injection). Simultaneously, the expression levels of antimicrobial peptides (AMPS), including anti-lipopolysaccharide factor (ALF) C1, C2, D1, and Crustin I, increased. Further study revealed that Knockdown of PIAS also enhanced STAT phosphorylation and translocation. In conclusion, PIAS negatively regulates JAK/STAT signaling by inhibiting the phosphorylation and translocation of STAT, which leads to the reduction of AMP expression in shrimp. Our results revealed a new mechanism of PIAS-mediated gene regulation of the STAT signal pathway.